Answers

2016-02-20T16:16:46+08:00
If substitution get any equation, I prefer the second one.
r+5=6s
r=6s-5

Substitute to the first equation
2(6s-5)+5s=0
12s-10+5s=0
17s-10=0
17s=10
s=0.59

Substitute to the equation we've equate
r=6(0.59)-5
r=-1.46

In eliminatio:
2r+5s=0
  r -6s=-5
Multiply the second equation by 2 to eliminate r
2r+ 5s=0
2r-12s=-10
Subtract the second equation from the first equation
17s=10
Divide both sides by 17
s=0.59
Substitute to any equation
2r+5(0.59)=0
2r+2.95=0
2r=-2.95
r=-1.47
Hope it helps =)
0